Efficacy of Non Surgical Measures for Managing Pancreatic Ascites - Katheresan, V.; Sivasankar, A.; Ponchidambaram, M.; Kesavan, B.; Somasekar, R. D. R. (New Horizons in Medicine and Medical Research Vol. 10, 2022)
Introduction: Pancreatic ascites (PA) refers to the exudative fluid collection in to the peritoneal cavity with rich amylase levels and is a rare entity. Chronic calcific pancreatitis related to alcohol abuse, tropical calcific pancreatitis etc. may present with pancreatic ascites secondary to pseudocyst rupture or ductal disruption. Objective: The objective of this case series is to evaluate the efficacy of non surgical measures in the management of pancreatic ascites in properly selected cases. Case Series: In this case series, we have described three patients of pancreatic ascites due to non ethanol induced chronic calcific pancreatitis who were treated successfully by non surgical measures. Two cases of PA were managed with image guided percutaneous catheter drainage (PCD) followed by transpapillary pancreatic duct (PD) stent placement and the third case was managed with PCD alone. All three patients had resolution of PA. Conclusion: Conservative management with PCD and PD stent placement helps in the effective management of PA in selected cases with fruitful results.